ANALISIS KARAKTERISTIK RUNWAY TERHADAP DIMENSI PESAWAT DI BANDARA HALUOLEO KENDARI - Syafar, Muh. Ismail; La Ode, Al Tafakur; Eko Prasetyo, Bagus; Soeparyanto, Try Sugiyarto; Alfarezi, Muhammad Hidayat (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
Airport is a certain area on land or water (including buildings, installations and airport operating equipment) for the movement of aircraft. The purpose of this study was to determine the characteristics of the runway to the dimensions of the aircraft at Haluoleo Kendari Airport and to determine the feasibility of the runway, taxiway, apron for the type of Airbus A330 aircraft at Haluoleo Kendari Airport. The method used in this study is to use a qualitative and quantitative research design using the FAA (Federal Aviation Administration) method with ICAO (International Civil Aviation Organization) rules. The results of the research on forecasting the growth of aircraft and passenger movements in 2026 with the number of passengers per year: 776,253,488 passengers, the number of passengers per year: 2,126 passengers, and the movement of aircraft per day during rush hour: 4 aircraft. From the calculation results, the required runway length is 3,100 m, with a runway width of 45 m. the required length of the taxiway obtained from the calculation is 279 m, the width of the taxiway is 23 m, while the area of the apron needed by the Airbus A330 is 6,671 m2. the calculation compared to the existing conditions, the length of the runway does not meet while the dimensions of the taxiway are suitable for Airbus A330 passage and for the apron owned by Haluoleo Kendari Airport it is feasible to be used as a stopping place for planned aircraft, because the dimensions of the existing apron are larger.